2008
DOI: 10.1007/s10876-008-0228-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Ionization Based Methods for the Generation of Polynuclear Oxo- and Hydroxo Group 6 Anions in the Gas-Phase

Abstract: Electrospray ionization (ESI) of the Lindqvist (n-Bu-(n = 1-6) species can be readily generated in the gas-phase upon varying the solvent composition as well as the ionisation conditions (typically the U c cone voltage). Complementary tandem mass experiments (collision induced dissociation and ion-molecule reactions) are also used aimed to investigate the consecutive dissociation of these species and their intrinsic gas-phase reactivity towards methanol. Special emphasis is paid to some of the key factors of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 52 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Even though fragmentation experiments give insight into the favored decomposition pathways of gas-phase clusters, they may also provide hints on potential intermediates that help to better understand the thermal assembly of POMs cluster anions. The peaks observed in the ESI-MS experiments (Supporting Information, Table S2 and Figure The observed set of peaks belong to the previously observed group of species with the general formula [Mo m O 3m+1 ] 2À and in agreement with the studies of Walanda, von Nagi-Felsobuki et al 32 and Llusar, Vicent et al 33 In this case, we did not detect any species of the protonated set with the general formula [HMo m O 3m+1 ] À since their formation depends greatly upon the solvent composition (aqueous and protic acidified media) and application of harsher ionization conditions (high collision energy values). 32,33 Consequently, the use of acetonitrile solution and application of mild ionization conditions during the course of our fragmentation experiments led only to the formation of the nonprotonated set, [Mo m O 3m+1 ] 2À , of species in the gas phase.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…Even though fragmentation experiments give insight into the favored decomposition pathways of gas-phase clusters, they may also provide hints on potential intermediates that help to better understand the thermal assembly of POMs cluster anions. The peaks observed in the ESI-MS experiments (Supporting Information, Table S2 and Figure The observed set of peaks belong to the previously observed group of species with the general formula [Mo m O 3m+1 ] 2À and in agreement with the studies of Walanda, von Nagi-Felsobuki et al 32 and Llusar, Vicent et al 33 In this case, we did not detect any species of the protonated set with the general formula [HMo m O 3m+1 ] À since their formation depends greatly upon the solvent composition (aqueous and protic acidified media) and application of harsher ionization conditions (high collision energy values). 32,33 Consequently, the use of acetonitrile solution and application of mild ionization conditions during the course of our fragmentation experiments led only to the formation of the nonprotonated set, [Mo m O 3m+1 ] 2À , of species in the gas phase.…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…In the context of the time-honored cytochrome P450, for example, the transfer of model metal porphyrins into the gas phase via laser evaporation or sputtering methods gave poor ion currents and instable signals, while this is straightforward with ESI, and it even works for the biologically relevant core species . In addition to the sampling of preformed ionic species from solution, a major feature of ESI is the ability to generate solvated ions in a controlled manner, thereby assisting in closing the gap between idealized studies in the gas phase and real chemistry in condensed media. , In the last few years, it has also been found that ESI, known and developed as a soft ionization method, can also be modified to rather hard conditions of ionization, which can be used to efficiently produced highly reactive species, , including a broad variety of transition-metal cluster ions via excessive fragmentation of suitable polynuclear precursors …”
Section: Experimental Methods For the Investigation Of Metal−ion Reac...mentioning
confidence: 99%
“…For example, it was possible to pinpoint the position of the vanadium ion in the {VMo 17 (VO 4 ) 2 } and {VW 17 (VO 4 ) 2 } Dawson‐like capsules15 and to distinguish between isomeric nonclassical Wells–Dawson [W 18 O 56 (XO 6 )] (X = W, Te or I) anions and to prove their intrinsic stability in the gas phase 16. CID techniques in the investigation of the Lindqvist [Mo 6 O 19 ] 2– and [W 6 O 19 ] 2– dianions17 proved to be a convenient source of smaller gas‐phase ions for subsequent gas‐phase reactivity studies towards methanol18 and shed light on the preferred nucleation steps leading to the Lindqvist dianions 19. We recently reported that the fragmentation reactions of some Keggin‐type {PW 11 O 39 Ru} POMs under CID conditions allowed the identification of the chemical environment of the noble metal site through the release of the specific neutral ligand (H 2 O, NO, N 2 or NH 3 ) attached at the Ru site 12a.…”
Section: Introductionmentioning
confidence: 99%